An Examination of Temporal and Spatial Trends of Growing Degree Days in Turkey - İlhami Doğan; Murat Karabulut (Doğal Afetler ve Çevre Dergisi)
The effects of global warming are not the same in every region of the world. Turkey in the Eastern Mediterranean Basin is one of the areas affected by this warming. Summer drought significantly felt in Turkey, where climatic conditions are constantly changing due to global warming. Therefore, it is necessary to continuously observed phenological events in the climate control. Various methods such as remote sensing systems, meteorological observations and species-based local evaluations are used in the investigation of phenological events. Growing degree-days (GDD) is one of the phenological prediction models based on meteorological variability. In this study, daily maximum and daily minimum temperature records of 147 meteorological observation stations were used to determine annual and seasonal trends of GDD in Turkey. GDD trends in various periods were determined by Mann-Kendall sequential statistics method. According to the survey, seasonal and annual trends in from 1970 to 2018 GDD are positive characters. In this process in the control of climate change, important phenological shifts have occurred in Turkey. BDG increases observed in summer; In agriculture and forestry, it may have increased drought-based heat stress even more. The positive trends in the study are thought to be effective on natural ecosystems through industry, agriculture, settlement, and natural resources. For this reason, basic climatic parameters such as temperature and precipitation need to be collected at more local scales.